ECONOMIC BENEFIT ANALYSIS ON IMPLEMENTATION OF PUBLIC TRANSPORTATION INVESTMENT POLICY IN THE CITY OF BANDA ACEH - Rina Kemala Sari; Mohd. Nur Syechalad; Muhammad Nasir (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2018)
AbstractThe purpose of this research is to analysed the effectof public transportation investment to the accelerationrate of traffic, to the growth of the governments'spending and income, also to evaluate the direct andindirect economic effect of this investment. The researchis done using cost benefit analysis with severalimportant assumptions. These assumptions were pickingto simplify the evaluation of the effects of the governmentinvestment on public transport in the city of Banda Aceh.The research results show that the development ofpublic transportation in the city of Banda Aceh affects toreduce the density of traffic in the city. The investmentalso results in the positive economic benefits for thecommunity. Though, for the government as the solecapital owner, the effect of this investment is notbeneficial.